Evaluation of training in guideline‐oriented biopsychosocial management of low back pain in occupational health services: Protocol of a cluster randomized trial. Issue 1 (4th March 2021) - Karppinen, Jaro; Simula, Anna Sofia; Holopainen, Riikka; Lausmaa, Mikko; Remes, Jouko; Paukkunen, Maija; Ussing, Kasper; Booth, Neill; Ryynänen, Katja; Koski, Tomi; Abbott, Allan; Öberg, Birgitta; et al.
Abstract: Background: To prevent low back pain (LBP) from developing into a prolonged disabling condition, clinical guidelines advocate early stage assessment, risk‐screening, and tailored interventions. Occupational health services recommend guideline‐oriented biopsychosocial screening and individualized assessment and management. However, it is not known whether training a limited number of health care professionals improves the management process. The primary objective of this study is to investigate whether training in the biopsychosocial practice model is effective in reducing disability. Furthermore, we aim to evaluate health‐economic impacts of the training intervention in comparison to usual medical care. Methods: The occupational health service units will be allocated into a training or control arm in a two‐arm cluster randomized controlled design. The training of occupational physiotherapists and physicians will include the assessment of pain‐related psychosocial factors using the STarT Back Tool and the short version of the Örebro Musculoskeletal Pain Screening Questionnaire, the use of an evidence‐based patient education booklet as part of the management of LBP, and tailored individualized management of LBP according to risk stratification. The control units will receive no training. The study population will include patients aged 18–65 with nonspecific LBP. The primary outcome is a patient‐reported Oswestry Disability Index from baseline to 12 months. By estimating group differences over time, we aim to evaluate the effectiveness of the training intervention in comparison to usual medical care, and to undertake an economic evaluation using individual patients' health care records (participant‐level data) and the participating units' registries (cluster‐level data). In addition, through interviews and questionnaires, we will explore the health care professionals' conceptions of the adoption of, the barriers to, and the facilitators of the implementation of the practice model. Discussion: The evaluation of training in the guideline‐oriented biopsychosocial management of LBP in occupational health services is justified because LBP represents an enormous burden in terms of work disability.